Nurses Knowledge about the Insertion Procedure for Peripherally Inserted Central Catheters in Newborns (Revista Latino-Americana de Enfermagem, 2010)
The right to practice the Peripherally Inserted Central Catheter (PICC) technique, mainly in neonatal intensive care units, was achieved by nursing and consists of efforts that lead to a new challenge: the improvement of the practice of this procedure. This study determined and evaluated the theoretical and practical knowledge acquired by nurses in qualification courses concerning aspects of PICC line insertion in the case of newborns. This descriptive and quantitative study used a questionnaire with nine questions to collect data. The study population was composed of 40 nurses qualified to insert a PICC line in newborns. According to the conceptual knowledge scale established for this study, the results reveal that the nurses have inadequate knowledge concerning the studied aspects, indicating the need for nurses to constantly update and improve their knowledge about this practice so as to better the quality of care delivered to newborns.